Signature Channels of Excitability no More: L-Type Channels in Immune Cells - Davenport, Bennett; Li, Yuan; Heizer, Justin W.; Schmitz, Carsten; Perraud, Anne-Laure (Frontiers in Immunology, 2015)
Although the concept of Ca2+ as a uni¬versal messenger is well established, it was assumed that the regulatory mechanisms of Ca2+-signal¬ing were divided along the line of electric excitability. Recent advances in molecular biology and genomics have however provided evidence that non-excitable cells such as immunocytes also express a wide and diverse pool of ion channels that does not differ as significantly from that of excitable cells as originally assumed. Ion channels and transporters are involved in virtually all aspects of immune response regulation, from cell differentiation and development, to activation, and effector functions such as migration, antibody-secretion, phagosomal maturation, or vesicular delivery of bactericidal agents. This comprises TRP channel family members, voltage- and Ca2+-gated K+- and Na+-channels, as well as unexpectedly, components of the CaV1-subfamily of voltage-gated L-type Ca2+-channels, originally thought to be signature molecules of excitability. This article provides an overview of recent observations made in the field of CaV1 L-type channel function in the immune context, as well as presents results we obtained studying these channels in B-lymphocytes.